2013
DOI: 10.1080/09670262.2013.786790
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, respiration and calcification in the Mediterranean crustose coralline algaLithophyllum cabiochae(Corallinales, Rhodophyta)

Abstract: Primary production and calcification responses to irradiance were investigated in Lithophyllum cabiochae, a crustose coralline alga from Mediterranean coralligenous communities, collected at c. 25 m depth in the Bay of Villefranche. Algae were maintained in aquaria at temperature and irradiance levels close to in situ conditions. Physiological measurements were performed using incubation chambers in the dark and in the light at different irradiance levels within the range of those measured in situ. Both photos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
44
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 37 publications
6
44
3
Order By: Relevance
“…The declines in CCA cover in response to CO 2 were steeper on these shaded bottom-sides compared to the top-sides of the tiles, suggesting that CCA may be physiologically more vulnerable to high CO 2 in low compared to high light environments. Previous physiological studies have shown that some CCA can continue to grow at high CO 2 in high light environments, but suffer dissolution in the dark2930. Our data also show the need for high light to maintain populations at high CO 2 in the field, with day-time calcification offsetting potential night-time dissolution.…”
Section: Discussionsupporting
confidence: 66%
“…The declines in CCA cover in response to CO 2 were steeper on these shaded bottom-sides compared to the top-sides of the tiles, suggesting that CCA may be physiologically more vulnerable to high CO 2 in low compared to high light environments. Previous physiological studies have shown that some CCA can continue to grow at high CO 2 in high light environments, but suffer dissolution in the dark2930. Our data also show the need for high light to maintain populations at high CO 2 in the field, with day-time calcification offsetting potential night-time dissolution.…”
Section: Discussionsupporting
confidence: 66%
“…They are the result of the building activities of algal and animal constructors, counterbalanced by physical, as well as biological, eroding processes. Because of their extent, biodiversity and production, coralligenous and maërl habitats rank among the most important ecosystems in the Mediterranean Sea [17][18][19][20][21] , and they are considered of great significance both for fisheries 22 and carbon regulation 23,24 .…”
mentioning
confidence: 99%
“…Based on the color and habit of the material illustrated, the material used by Martin et al. (,b; as L. cabiochiae ) appears to be L. stictiforme (clade 1). Conversely, the thalli depicted by Garrabou and Ballesteros () cannot be reliably identified.…”
Section: Discussionmentioning
confidence: 99%